Comparison of Functional Variants in IFNL4 and IFNL3 for Association with Hepatitis C Virus Clearance - O’Brien, Thomas R. (J Hepatol, 2015)
BACKGROUND & AIMS: Genetic polymorphisms within the interferon lambda (IFN-λ) region are strongly associated with hepatitis C virus (HCV) clearance; the IFNL4-ΔG/TT (rs368234815) polymorphism, which controls generation of the IFN-λ4 protein, is more strongly associated with HCV clearance than rs12979860 (the ‘IL28B variant’). An IFNL3 3′ untranslated region polymorphism (rs4803217) has been proposed as a causal variant that may affect HCV clearance by altering IFNL3 mRNA stability. METHODS: We compared IFNL4-ΔG/TT and rs4803217 for association with response to pegylated-IFN-α/ribavirin in the VIRAHEP-C and HALT-C trials, and spontaneous HCV clearance in the ALIVE, UHS and WIHS studies. Genotyping was performed with TaqMan assays. We compared differences in mean reduction in HCV RNA levels by genotype and haplotype. For HCV clearance, we calculated p-values comparing c-statistics for IFNL4-ΔG/TT and rs4803217 genotypes by a bootstrap approach. RESULTS: Among European Americans, linkage disequilibrium between IFNL4-ΔG/TT and rs4803217 was strong (r(2)=0.89–0.99) and there were no significant differences between the variants. In African American (AA) individuals enrolled in VIRAHEP-C, HCV RNA at treatment day 28 was more strongly associated with IFNL4-ΔG/TT than rs4803217 (p=0.003); the IFNL4-ΔG:rs4803217-G haplotype, which includes the putatively favorable IFNL3 allele, was actually associated with the poorest day 28 response (p=0.03, comparison to IFNL4-ΔG:rs4803217-T haplotype). Among AA participants, associations were stronger for IFNL4-ΔG/TT than rs4803217 for undetectable HCV RNA at week 24 in Virahep C (p=0.03) and week 20 in HALT-C (p=0.03), as well as for spontaneous HCV clearance (p=0.048). CONCLUSION: IFNL4-ΔG/TT is the primary IFN-λ region polymorphism for impaired HCV clearance.